2010
DOI: 10.1053/j.ackd.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes in the Aging

Abstract: The elderly population in the United States continues to grow and is expected to double by 2050. With aging there are degenerative changes in many organs and the kidney is no exception. After age forty there is an increase in cortical glomerulosclerosis and a decline in both glomerular filtration rate and renal plasma flow. These changes may be associated with an inability to excrete a concentrated or a dilute urine, ammonium, sodium, or potassium. Hypernatremia and hyponatremia are the most common electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 93 publications
0
48
0
1
Order By: Relevance
“…doubly labelled water) has not been measured to test the association between it and 24 h urinary K. The measurement of 24 h urinary K excretion has the advantage over other biochemical methods of being non-invasive and inexpensive. It should be noted, however, that K excretion via the urine varies depending on age, sex, the amount of physical activity undertaken and BMI (10,(43)(44)(45) , for which adjustment was made in the present study. Furthermore, it must be stated that using the 24 h urine method has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…doubly labelled water) has not been measured to test the association between it and 24 h urinary K. The measurement of 24 h urinary K excretion has the advantage over other biochemical methods of being non-invasive and inexpensive. It should be noted, however, that K excretion via the urine varies depending on age, sex, the amount of physical activity undertaken and BMI (10,(43)(44)(45) , for which adjustment was made in the present study. Furthermore, it must be stated that using the 24 h urine method has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The fi ndings also suggest that being dependent or less mobile contribute to hypernatraemia (only 22% of patients were living at home independently, whereas 64% were admitted from care homes) as does having dementia (53% of patients). Previous studies have shown that electrolyte imbalances are more prevalent in older people, 2,3,8 those living in institutions 9 and those with Alzheimer's dementia. 10 Only 12 of the 55 patients who were admitted lived independently at home.…”
Section: Discussionmentioning
confidence: 99%
“…This is most commonly seen in infants and in adults with impaired mental status, particularly older patients. 2,3 Older patients might also have a diminished thirst response to osmotic stimulation via an unknown mechanism. 4,5 Hypernatraemia is often poorly managed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypokalemia is an important electrolyte disorder occasionally seen in elderly patients [1]. The serum potassium (K) level is determined mainly by the balance among oral intake, distribution, and excretion via the kidney and the gastrointestinal tract [2].…”
Section: Introductionmentioning
confidence: 99%